Number of Erythrocytes of White Rats (Rattus norvegicus) Sonded with a Combination of Porang Tuber and Moringa Leaf Extract - Anggitasari, Alya; Setyaningsih, Endang (Universitas Muhammadiyah Surakarta, 2023)
Overcoming obesity which is increasing in the pandemic era. Obesity or overweight is an abnormality in the amount of body weight that results in excessive accumulation of body fat and can pose a risk of other diseases. This also affects the supply of the number of erythrocytes that enter the body. This study aims to determine the number of erythrocytes of obese white rats (Rattus norvegicus) that were sounded with a combination of pouring tuber glucomannan (Amorphophallus mulleri Blume) and moringa leaf extract. This research method used a true experimental which was prepared using a Completely Randomized Design (CRD) in the form of a Posttest Only Control Design. The data obtained were analyzed using One Way ANOVA SPSS version 20 followed by the DMRT test. The results of this study indicated that the combination of pouring tuber glucomannan and moringa leaf extract affected increasing the number of erythrocytes in obese white rats. Administration of pouring tuber glucomannan and moringa leaf extract increased the number of erythrocytes, with the order of increasing P7 (60:40), P5 (80:120), and P3 (100:100). With these results, it can be concluded that the combination of pouring tuber with moringa leaf extract is effective in increasing the number of erythrocytes in obese people.